Prediction and inference of dynamics in quantum plasmas - Larder, B (2020)
Quantum plasmas arise in a range of physical contexts, from planetary interiors to Inertial Confinement Fusion experiments. We require sophisticated numerical approaches to find the structural and dynamic properties of these complex, many-body quantum systems; diverse in accuracy and applicability, these computational approaches each have their own strengths and (often ignored) weaknesses.